ISLAMIC WORK ETHICS AS AN ADDITIONAL CHARACTERISTIC OF INTERNAL CORPORATE GOVERNANCE MECHANISMS - Talal Salem Annakoua; Fadzila Azni Ahmad; Shahir Akram Hassan (Journal of Islamic, Social, Economics and Development, 2024)
The separation of ownership and management has resulted in conflict of interests between the owners (principals) and managers (Agents). To mitigate this problem of agency, corporate governance mechanisms has been introduced. Corporate Governance Mechanisms (CGMs) aims at constraining managers from adopting self-interest behavior. However, financial scams and scandals resulting from this behavior are still seen worldwide. This paper attempts to discuss the failure of CGMs in preventing financial scams and frauds, and the importance of characterizing these mechanisms by Islamic Work Ethics (IWEs). This research uses qualitative approach through reviewing the literature to gain broad insight of the issues related to Corporate Governance (CG) and IWEs. The findings show that IWEs can provide a protection shield to CGMs against any misconduct or corporate crime. The study urges regulators to stop limiting their focus on merely technical CGMs characteristics such as size, independence…etc. IWEs can provide a clear explanation why financial scandals and frauds occur in Islamic institutions that have CGMs technically meeting the requirements of the laws and regulations, while not characterized by IWEs.